Optimasi Basis Formulasi Sediaan Handsanitizer Gel Ekstrak Daun Sirih Hitam (Piper betle var nigra) Sebagai Antibakteri: Optimization of the Hand Sanitizer Gel Preparation Base for Black Betel Leaf Extract (Piper betle var nigra) as an antibacterial - Felina Alfiany; Novita Eka Kartab Putri; Fajar Prasetya (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Black betel leaf (Piper betle var. nigra) is one of the plants that has the potential as an antibacterial. This research is a laboratory experiment and aims to determine the optimum concentration of hand sanitizer gel base which will then be used in the formulation of hand sanitizer gel preparations with the active ingredient of black betel leaf. Optimization was carried out for 7 days by looking at the physical properties of the gel preparation, namely organoleptic, homogeneity, pH test, viscosity, and spreadability test. Handsanitizer gel was made in three formulas with three different concentrations of Carbopol 940, namely A, B, and C. The results obtained in the evaluation of the organoleptic test were observed in clear color, semisolid dosage form and smelled of Carbopol 940. Homogeneity test was indicated by the absence of granules. rough on the preparation. The pH test is the pH of the gel preparation which is stable at pH 7. The dispersion test of 5-7 cm shows a semisolid consistency which is very comfortable to use. The viscosity test showed that the gel viscosity was in the range of 1,206 cps - 1,820 cps. The results of the evaluation of the optimum hand sanitizer gel base are obtained if it has good physical quality and meets the criteria for gel preparation. Based on the evaluation results on the optimization of the hand sanitizer gel base, it was obtained that the Carbopol 940 gel base with a concentration of A had met the criteria for making gel preparations.